Canadian primal : poets, places, and the music of meaning - Dickinson, Mark, 1973- (McGill-Queen's University Press, 2021)
"Meaning is all around us, but because of the way we live as moderns, we are mostly unable to perceive it. Or so say the Thinking and Singing poets, one of the most remarkable gatherings of artist-thinkers in Canada since the Group of Seven. They are Robert Bringhurst, Dennis Lee, Tim Lilburn, Don McKay and Jan Zwicky. For more than fifty years, they have been taking short trips into that more meaningful world and leaving clues to its whereabouts in their poems, essays, and other writings. Canadian Primal is the first group biography of the Thinking and Singing poets. Mark Dickinson describes how they each found their way to that richer reality, introduces the guides and teachers who affirmed what they saw, and tracks how they came to poetry as a way of being with that world. Dickinson considers some of the most important moments in their lives - 'primal' moments when they felt the touch or heard the call of that larger world - that allowed them to move beyond the ways of thinking and structures of life in which they'd been trapped. Drawing on dozens of field visits and thousands of letters and e-mails with its subjects, Canadian Primal is literary biography reconceived as an adventure of the mind, body, and spirit. Ebullient, intelligent and eminently readable, it reminds us that we can live on the earth in a different way, true to the defining experiences of our lives, surrounded by meaning and presence beyond our imagining."--